2011
DOI: 10.4317/medoral.16.e296
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of odontogenic sinus tracts in 728 endodontically treated teeth

Abstract: Objectives: The primary aim of this study was to assess the prevalence of sinus tracts in endodontically treated teeth in an Iranian population. The second aim was to seek and analyze the relationship between the clinically detected sinus tracts and factors such as sex, age, tooth type and location. Study design: A total of 728 patients` records and radiographs were reviewed of 427 females and 301 males for demographic data, preoperative pulpoperiapical status of treated teeth and the presence of sinus tract. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 13 publications
2
43
2
Order By: Relevance
“…A study published by Miri et al [13] which was realized in Iran in 1,527 patients with a personal history of endodontic treatment, it was found a frequency of a sinus tract of 9.9% in contrast with another study reported by Sadeghi et al [14] in 2011 in a very similar population with the same procedence and under canalicular therapy, in 728 patients it was set a prevalence of 14.7% [13,14] submitting the patient to unnecessary antibiotic treatments, biopsies, resections, and even radiotherapy, with a not so favorable outcome and a recurrence of the fistula [1][2][3]. Patients with or cutaneous fistulas it has been thought that odontocutaneous fistulas are more frequent in children and adolescents, due to the fact that the alveolar processes are not fully developed, although, it has been seen in patients older than 20 years of age [9].…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…A study published by Miri et al [13] which was realized in Iran in 1,527 patients with a personal history of endodontic treatment, it was found a frequency of a sinus tract of 9.9% in contrast with another study reported by Sadeghi et al [14] in 2011 in a very similar population with the same procedence and under canalicular therapy, in 728 patients it was set a prevalence of 14.7% [13,14] submitting the patient to unnecessary antibiotic treatments, biopsies, resections, and even radiotherapy, with a not so favorable outcome and a recurrence of the fistula [1][2][3]. Patients with or cutaneous fistulas it has been thought that odontocutaneous fistulas are more frequent in children and adolescents, due to the fact that the alveolar processes are not fully developed, although, it has been seen in patients older than 20 years of age [9].…”
Section: Discussionmentioning
confidence: 82%
“…The average of the patient age varies: Sadeghi et al [14] reported an age range of 10-69 years; in the Guevara et al [15] study the mean was 45 years with a higher presentation of sinus tracts in patients older than 51 years. In the Slutzky et al [16] the mean was 32.2 years [14,15]. According to gender, the presence of odontocutaneous fistulas can vary: Guevara et al [15] found 53% of women with this condition and Miri et al [13] in a 9.1% and Huang et al [17] in 45.3% of women, meanwhile; Sadeghi et al [14] did not find significant differences between men and woman [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations